Perception, Attitude, and Knowledge of Nursing Students towards Wet Cupping Therapy (Hijamah) - Syahruramdhani Syahruramdhani; Muhammad Taupikurrahman; Altaf Maulana Pasha (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: Complementary and Alternative Medicine (CAM) is a part of the health system that is well known and useful worldwide. One of the therapies used by many people is wet cupping therapy (hijamah). Nowadays, wet cupping therapy (hijamah) is taught in nursing and medical school.Objective: The study investigates the perception, attitude, and knowledge of nursing students toward wet cupping therapy (hijamah).Method: This study was quantitative research that uses descriptive research design and cross-sectional approaches. The sampling technique used was purposive sampling with 85 respondents. The data were collected using questionnaires and analyzed with bivariate analysis.Result: The result showed that the perceptions of the respondents were mostly in the average category, with the best perception of respondents is in the benefit component (76.5%). Respondents have good view of cupping therapy as is useful as a form treatment, and is more practical and affordable. The respondents' attitudes and knowledge were in the average category, which was 58.8% and 68.2%.  This study showed that most respondents already understand that cupping (hijamah) is a treatment with contraindications to specific health conditions. Respondents also could show the basic scientific concepts of cupping and hadiths that explained cupping. However, some respondents still think that cupping (hijamah) can be applied for all ages.Conclusion: In conclusion, respondents' perceptions, attitudes, and knowledge toward wet cupping therapy (hijamah) were still insufficient in some aspects.